2008
DOI: 10.1029/2008ja013211
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic signatures and conjugate features of low‐latitude plasma blobs as observed by the CHAMP satellite

Abstract: [1] We investigated the magnetic signatures of plasma blobs, as observed by the CHAMP satellite. In total, we have identified 52 blobs with clear density enhancements and magnetic signatures. In each blob the magnetic field strength was depressed, and the components perpendicular to the main magnetic field direction showed fluctuations. The variation in magnetic field strength implies that the enhanced plasma pressure is balanced by a magnetic pressure reduction, and the deflection in the perpendicular compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 30 publications
10
60
0
Order By: Relevance
“…At ionosphere mid-latitudes, the nighttime electron density enhancement has been observed and reported by previous studies (e.g., Bailey et al 1991;Farelo et al 2002;Dabas and Kersley 2003;Luan et al 2008;Park et al 2008;Chen et al 2011Chen et al , 2012Chen et al , 2013Lin et al 2011;Rajesh et al 2016). This density-enhanced ionospheric feature appeared more frequently during solar minimum conditions (Bailey et al 1991), and it is suggested to be caused by larger downward plasma flux from the plasmasphere during the nighttime (Mikhailov et al 2000;Farelo et al 2002;Dabas and Kersley 2003).…”
Section: Introductionmentioning
confidence: 51%
“…At ionosphere mid-latitudes, the nighttime electron density enhancement has been observed and reported by previous studies (e.g., Bailey et al 1991;Farelo et al 2002;Dabas and Kersley 2003;Luan et al 2008;Park et al 2008;Chen et al 2011Chen et al , 2012Chen et al , 2013Lin et al 2011;Rajesh et al 2016). This density-enhanced ionospheric feature appeared more frequently during solar minimum conditions (Bailey et al 1991), and it is suggested to be caused by larger downward plasma flux from the plasmasphere during the nighttime (Mikhailov et al 2000;Farelo et al 2002;Dabas and Kersley 2003).…”
Section: Introductionmentioning
confidence: 51%
“…Kil and Heelis, 1998;Huang et al, 2001;Park et al, 2005;Stolle et al, 2006), and in the Southern winter Hemisphere where blobs are frequently observed (e.g. Watanabe and Oya, 1986;Park et al, 2008b). This event is accompanied by EPBs between ±3 • GLAT showing magnetic field deflections outward and westward.…”
Section: Discussionmentioning
confidence: 99%
“…For the other one (near 04:10 UT on 18 January 2002, shown in Fig. 1 of Park et al, 2008b), the polarization angle is 150 • (i.e. westward tilt) and the peak FAC density is of the order of 0.1 µA/m 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations